Identifying cytoplasmic proteins that affect receptor clustering using fluorescence resonance energy transfer and RNA interference. - Dibya, D.; Sander, S.; Smith, E.A. (Analytical and Bioanalytical Chemistry, 2009)
Unraveling the complex, dynamic organization of the cell membrane can provide vital information about many aspects of cellular functions. Reported herein is a method for identifying cytoplasmic proteins that affect cell membrane protein organization. RNA interference (RNAi) is used to reduce the expression of select cytoplasmic proteins and a fluorescence resonance energy transfer (FRET) assay is used to measure changes in receptor microclustering. The advantage of this assay is that it does not require attaching fluorescent tags to the receptor. A change in energy transfer after reducing the expression of a cytoplasmic protein provides information about the protein's role in altering receptor organization. As a demonstration of the method, cytoplasmic proteins involved in integrin microclustering have been identified. The cytoplasmic proteins targeted in this study include: dreadlock, integrin-linked kinase, paxillin, steamer duck, vinculin, rhea, focal adhesion kinase, and actin 42A. Reducing the expression of vinculin, paxillin, rhea, and focal adhesion kinase increased integrin microclustering, as measured by an increase in energy transfer in cells expressing alphaPS2CbetaPS integrins. No change in integrin microclustering was measured in a control cell line. Integrin mutants exhibited different microclustering properties compared to the wild-type integrins after reducing the expression of the listed cytoplasmic proteins. The results demonstrate the utility of this assay format, and provide insight into the function of cytoplasmic proteins in integrin microclustering.